Management of entrepreneurial structures in agrarian sector of economy of the North Caucasian federal district - V. D. Nebessky (Вестник Северо-Кавказского федерального университета, 2022)
The article provides a focus on the priorities in the strategy for the development of the agricultural area in the North Caucasus Federal District. There is an analysis of the programmes for comprehensive development of certain areas in the district, as well as the systems for managing entrepreneur structures and their efficiency